Experimental treatment of stroke in spontaneously hypertensive rats by CD34+ and CD34- cord blood cells - Egger, Dietmar; Buhrle, Christian; Gunther, Albrecht; Reich, Doreen; Geiger, Kathrin; Kowalski, Ina; Boltze, Johannes; Kamprad, Manja; Emmrich, Frank (GMS German Medical Science, 2005)
Human umbilical cord blood as a source of stem cells has recently been reported in experimental treatment of cerebral disorders. However, little is known about the nature of cells and cellular mechanisms leading to neurofunctional improvement. Here we investigated the potential of separated CD34+ versus CD34- human umbilical cord blood cells (HUCBC) to promote functional recovery following stroke. The experiments were performed in spontaneously hypertensive (SH) rats, known for a risk profile comparable to stroke patients. After three weeks of behavioral training in the RotaRod and Beamwalk test arrays, stroke was induced by permanent middle cerebral artery occlusion (MCAO). For cell therapy, 1x106 cryopreserved cells were administered systemically between 8 and 10 hours after MCAO. The behavioral tests were performed together with a neurological severity score (mNSS) until day 29 to assess neurofunctional disabilities. Nearly complete functional remission was observed with both subpopulations CD34+ as well as CD34- cells. To localize cells histologically, they were labeled with a fluorescence dye (CFSE) before injection. Again, after administration of CD34+ as well as CD34- cells, CFSE labelled cells were found that accumulated in the border zone between the central necrosis of the ischemic lesion and functional brain tissue, thus indicating active attraction towards the lesion for both cell populations. Immunohistology with anti-CD68 and antibodies to human neuronal markers (NF-L, chromogranin) indicated an accumulation of human and rat monocytes in the border zone of the lesion while neuronal cells of human origin could not be detected in host brains.